Calculer chaque expression en écrivant les étapes.
A = 6 – 4 – 9 + 2 – 7
B = -29 + 20 – 33 + 29 + 13
C = (+3) – (-1) + (-2,5) – (+ 4,2)
D = -6 + (-3) – (+2, 5) – (2 – 4,5)
F = 14 – 7 + 3 – 14 + 10 – 5
Merci :)

2

Réponses

Meilleure réponse !
2014-02-28T16:50:09+01:00
A = 6 – 4 – 9 + 2 – 7
A = 2 - 9 + 2 - 7
A = -7 + 2 - 7
A = - 5 - 7
A = -12

B = -29 + 20 – 33 + 29 + 13
B = - 9 - 33 + 29 + 13
B = -42 + 29 + 13
B = -13 + 13
B = 0

C = (+3) – (-1) + (-2,5) – (+ 4,2)
C = 3 + 1 - 2,5 - 4,2
C = 4 - 2,5 - 4,2
C = 1,5 - 4,2
C = -2,7

D = -6 + (-3) – (+2, 5) – (2 – 4,5)
D = - 6 - 3 - 2,5 - (-2,5)
D = - 6 - 3 - 2,5 + 2,5
D = - 9 - 2,5 + 2,5
D = - 11,5 + 2,5
D = - 9

F = 14 – 7 + 3 – 14 + 10 – 5

F = 7 + 3 - 14 + 10 - 5
F = 10 - 14 + 10 - 5
F = - 4 + 10 - 5
F = 6 - 5
F = 1
2014-02-28T17:19:02+01:00
Bonsoir,

A= 6-4-9+2-7
A= 2-9+2-7
A= -7+2-7
A= -5-7
A= -12

B= -29+20-33+29+13
B= -9-33+29+13
B= -42+29+13
B= -13+13
B= 0

C= (+3)-(-1)+(-2,5)-(+4,2)
C= 3+1-2,5-4,2
C= 4-2,5-4,2
C= 1,5-4,2
C= -2,7

D= -6+(-3)-(+2,5)-(2-4,5)
D= -6-3-2,5-(-2,5)
D= -6-3-2,5+2,5
D= -9-2,5+2,5
D= -11,5+2,5
D= -9

F= 14-7+3-14+10-5
F= 7+3-14+10-5
F= 10-14+10-5
F= -4+10-5
F= 6-5
F= 1

bonne soirée
merci meme si c'est deja fait mais merci bcp